Overview of country nutritional status - Tee, E. Siong; Khor, Geok Lin
The country has undergone tremendous socio-economic development since it gained Independence. Health indicators such as life expectancy at birth, and infant, toddler and maternal mortality rates have been improving steadily. Food Balance Sheet data also indicate increases in per capita availability of protein and calorie. These data show that the nutritional status of Malaysians have been improving over the years. However, due to the problem of inequity, such national data do not reflect the existence of considerable variations in the nutritional status of different communities in various parts of the country. Indeed, recent studies have indicated that considerable amount of mild to moderate malnutrition occurs in various poverty rural and urban communities, although severe protein-energy malnutrition is not frequently reported. Mejor nutritional deficiency problems encountered by various segments of the population will be highlighted.